Determining the suitability of mass spectrometry for understanding the dissolution processes involved with pharmaceutical tablets. (12th May 2015) - Lewis, Claire; Ray, Andrew; Bristow, Tony; Wren, Stephen
<x xml:space="preserve">Abstract</x> Rationale A current challenge for analytical chemists is the development of the measurement systems and approaches required to understand dynamic processes such as tablet dissolution. The design and development of oral tablets could be improved by the availability of detailed information about the rates of release of the individual tablet components. Small footprint mass spectrometry (MS) systems are gaining use for on‐line reaction monitoring because of their ability to rapidly determine multiple reactant, intermediate, and product species. We have therefore assessed the utility of such MS systems to the study of dissolution processes. Methods Aqueous dissolution media containing phosphate and other non‐volatile buffer salts were pumped from a standard USPII dissolution vessel through an active splitter and back. The splitter sampled the dissolution stream and diluted it into a make‐up flow which was pumped to a small single quadrupole mass spectrometer. Single ion monitoring was used to quantify the ions of interest. Three different bio‐relevant dissolution media were studied to gauge the effect of the sample matrix. Results Individual dissolution profiles were obtained from a tablet containing three drugs, and lactose as the soluble filler. This was successfully demonstrated with three different bio‐relevant media designed to reflect the pH of the different sections of the human gastro‐intestinal tract. Component concentrations as low as 0.06 µg/mL (representing 1% dissolution) were detected. The MS dissolution profiles correlated with the visual observation of tablet dissolution. MS gave linear responses with concentration for the individual components, although analysis of the tablet solution indicated that ion suppression is an area for further investigation. Conclusions An on‐line MS system was used to determine the individual dissolution profiles of three drugs and lactose as they were released from the same tablet. The level of each of these components in solution was determined every 10 seconds, and each had a similar release profile. The dissolution profiles were determined using inorganic buffer solutions at three different bio‐relevant pHs. Copyright © 2015 John Wiley & Sons, Ltd.